Experimental investigation of transient contact heat transfer between 300M and 5CrNiMo. (May 2016) - Zhu, Zhi; Zhang, Liwen; Zhang, Chi; Li, Ruiqin; Gu, Sendong
Highlights: The thermal contact conductance at the interface between 300M and 5CrNiMo based on the transient method were measured. The effects of the initial temperature of the 300M specimen, the interfacial pressure on the thermal contact conductance were evaluated. The effects of the oxide layer and the graphite lubricant on the thermal contact conductance were evaluated. Abstract: The contact heat transfer between 300M steel and 5CrNiMo die steel has an important influence on the hot forging process of 300M steel. The accurate thermal contact conductance data are needed for the optimal design and numerical simulation of the hot forging process of 300M steel. Consequently, in this study, a set of new experimental apparatus and relevant procedure were developed to measure the thermal contact conductance at the interface between 300M and 5CrNiMo based on the transient method. The effects of the initial temperature of the 300M specimen, the interfacial pressure, the oxide layer and the graphite lubricant on the thermal contact conductance were evaluated.